Effect of intermittent normobaric hypoxia on the morphological changes in the respiratory part of lungs in different seasons of the year - Roman Yanko; Michail Levashov; Elena Chaka; Irina Litovka (Kazimierz Wielki University, 2018)
The purpose of this work was to study and compare the effect of intermittent normobaric hypoxia on the morphological and biochemical indices of the functional state and structure of the respiratory part of the lungs in the spring and autumn. The experimental rats were daily exposed to hypoxic gas mixture (12% oxygen in nitrogen) in intermittent mode: 15 minutes deoxygenation / 15 minutes reoxygenation for 2 hours. The duration of the experiment was 28 days. The histological preparations were made by the standard methods. The slides were photographed using a digital camera on the microscope «Nikon» (Japan). The morphometric analysis was performed on digital images with using the computer program "Image J". In the lung tissue was determined the concentration of total hydroxyproline and lipids. The results of our studies showed the seasonal differences in the effect of intermittent normobaric hypoxia on the morpho-functional state of respiratory part of the lungs. It can be related to the features of its activity in the spring and autumn. In spring, during a period of lesser activity of respiratory part of the lung, prolonged exposure to intermittent normobaric hypoxia slightly increases its functional activity. But in autumn, during a period of greater activity, it decreases. Thus, the use of intermittent normobaric hypoxia makes it possible to smooth seasonal differences in respiratory part of the lung activity.